Implementation of a Medication Reconciliation Process in an Internal Medicine Clinic at an Academic Medical Center - Kathryn M. Holt; Amy N. Thompson (MDPI AG, 2018)
Discrepancies in medication orders at transitions of care have been shown to affect patient outcomes in a negative way. The Joint Commission recognizes the importance of medication reconciliation through their National Patient Safety Goals, with an emphasis placed on maintaining accurate medication information for each patient. The primary objective of this study was to assess the effectiveness of implementing a medication reconciliation process in an internal medicine clinic at an academic medical center. A retrospective chart review of patients seen at an Internal Medicine Clinic within and Academic Medical Center, a continuity and teaching clinic for Internal Medicine residents and faculty practice clinic, was conducted. Nursing staff were educated by PharmDs to perform a standardized medication history during the triage process. Medication reconciliation data was analyzed for 3263 patients from 1 August 2014 to 27 February 2015. A total of 4479 discrepancies were found through this process, with the majority (71%) of discrepancies being medications on the list that patient was no longer taking. This project illustrated to our nursing and physician staff the need for regular thorough review of the patient medication list.